Development of UHTCMCs via water based ZrB2 powder slurry infiltration and polymer infiltration and pyrolysis. Issue 15 (December 2020) - Servadei, Francesca; Zoli, Luca; Galizia, Pietro; Vinci, Antonio; Sciti, Diletta
Highlights: Ultra-high modulus pitch-based Cf reinforced ZrB2 -SiC matrix composites were studied. Water-based slurry impregnation followed by PIP with polycarbosilane were combined. Flexural strength ranged from 190 to 500 MPa on the base of the fibre architecture. The formation of a borosilicate glass guaranteed an optimal resistance to oxidation. Elevated temperature properties of material are correlated to pyrolysis temperature. Abstract: Cf /ZrB2 -SiC ultra-high temperature composites were manufactured via aqueous slurry impregnation coupled with polymer infiltration and pyrolysis, using a allylhydrido polycarbosilane precursor. For the first time we used ultra-high modulus pitch-based carbon fibres for the PIP process, investigating three different architectures, 0/0°, 0/90°, and 2D. Microstructure, mechanical properties and oxidation resistance in air at 1650 °C were investigated. As expected, the mechanical properties showed the tendency to decrease with increase of the preforms complexity, due to the higher amount of flaws and residual stresses. For instance, the flexural strength was approaching 500 MPa for 0/0°, 370 MPa for 0/90° and 190 MPa for 2D. The materials showed an optimal resistance to oxidation at 1650 °C thanks to formation of a viscous borosilicate glass that guaranteed a self-healing functionality.